Over a million students use our free study notes to help them with their homework
22x - 6(2x ) + 5 = 0let y = 2xy2 - 6y + 5 = 0(y-5)(y-1) = 0 y=5, y=12x = 5, therefore, x = log25 = 2.32 (3 s.f.)2x = 1, therefo...
Firstly, establish that the correct method to do this is via differentiation: specifically implicit differentiation. To find the gradient, we need to find dy/dx. The differential with res...
As f(x) is in the form of u(x)/v(x) we can apply the rule that f'(x) = (u'(x)*v(x) - v'(x)*u(x))/(v(x)2), pulled from the C3 formula booklet.If u(x) = sin(2x) then u'(x) = 2cos(2x)....
f(f (x) )= f( (1-x)/(1+x) ) = (1-(1-x)/(1+x))/(1+(1-x)/(1+x))where you replace x by (1-x)/(1+x). Multiply the top and bottom of the fraction by (1+x) to get ((1+x)-(1-x))/((1+x)+(1-x)) which simplifies t...
The normal distribution is a distribution we can use when we know the mean and the standard deviation of a population, to work out probabilities that a certain even will occur.The main properties of...
←
688
689
690
691
692
→
Internet Safety
Payment Security
Cyber
Essentials